Variations of Hawk Mimicry Traits in the Four Sympatric Cuculus Cuckoos - Go, Jun-Seo; Lee, Jin-Won; Yoo, Jeong-Chil (Frontiers in Ecology and Evolution, 2021)
A well-known visual signal, hawk-like features such as yellow eyes and feet, and barred underparts have been recognized as coevolutionary traits obtained against host defense in Cuculus cuckoos. However, the variation of these traits within and among species remains poorly understood because empirical studies quantifying these traits are limited in terms of the number of studies and the number of species concerned, and mostly depend on museum collections. In this study, we quantified and compared these traits as well as other new features (e.g., inner wing spot and underpart background color) in the four sympatric Cuculus cuckoos (C. poliocephalus, C. micropterus, C. optatus, and C. canorus) that were wild-captured in South Korea. We found that the yellow color of the eye ring and feet was fairly consistent across the four species. However, the iris color appeared to vary within a species (e.g., between sexes) and varied more substantially among species from nearly black in C. micropterus to bright yellow in C. canorus. In addition, there were significant differences among species with respect to the thickness of the underpart bars, from the thinnest in C. canorus to the thickest in C. micropterus. We also found that the underpart color (pure white versus yellowish brown) and the number of inner wing spots varied within and among species. These results indicate that although hawk-like traits are widely present in Cuculus cuckoos, detailed quantitative features of these traits vary across species. We discuss the potential reasons that generate such variations and suggest future directions to increase our understanding of visual signals in avian brood parasitism.